PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL PADA IPM DENGAN VARIABEL PEMODERASI DANA ALOKASI UMUM - Pradnyantari, Putu Milan; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
PAD and Capital Expenditure allegedly not always a linear effect on Human Development Index, due to contingent factors that affect this relationship, the factor is General Allocation Fund. This study aims to determine the effect of PAD and Capital Expenditure on HDI, as well as the effect of PAD and Capital Expenditure by moderating DAU on IPM. The study covers eight counties and one city in Bali Province of observations from 2010 to 2015. This study uses secondary data obtained from the Bali Provincial Finance Bureau and the Central Bureau of Statistics. Data analysis techniques used Moderated Regression Analysis. The test results indicate that the PAD can improve the Human Development Index variable Capex while lowering the level of Human Development Index in the District/City of Bali Province. General Allocation Fund strengthen the influence of PAD to the HDI but can weaken the influence of Capital Expenditure in the HDI.
Keywords: Locally-generated revenue, Capital expenditure, General Allocation Fund, Human Development Index